2014
DOI: 10.4049/jimmunol.1400389
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB–Inducing Kinase in Thymic Stroma Establishes Central Tolerance by Orchestrating Cross-Talk with Not Only Thymocytes but Also Dendritic Cells

Abstract: Essential roles of NF-κB–inducing kinase (NIK) for the development of medullary thymic epithelial cells (mTECs) and regulatory T cells have been highlighted by studies using a strain of mouse bearing a natural mutation of the NIK gene (aly mice). However, the exact mechanisms underlying the defect in thymic cross-talk leading to the breakdown of self-tolerance in aly mice remain elusive. In this study, we demonstrated that production of regulatory T cells and the final maturation process of positively selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Thus, the lack of autoimmunity in the report by Birnberg et al, was attributed to the presence of pDCs and epidermal Langerhans cells (LCs) that were absent in the experimental system used by Ohnmacht et al in which DC ablation correlated with development of fatal autoimmunity [16, 17]. Similarly, mouse models with mutations affecting signaling through the NFkB pathway such as the alymphoplasia ( aly/aly ) mice develop chronic autoimmunity resembling Sjorgren’s syndrome despite impaired mTEC development and reduced numbers of tDC subsets [30, 31], again suggesting that severe disruptions of more than one subsets of thymic APCs are required for development of autoimmunty. Consistent with this, it was shown that depletion of DCs down to 5% of physiologic levels can still efficiently induce tolerance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lack of autoimmunity in the report by Birnberg et al, was attributed to the presence of pDCs and epidermal Langerhans cells (LCs) that were absent in the experimental system used by Ohnmacht et al in which DC ablation correlated with development of fatal autoimmunity [16, 17]. Similarly, mouse models with mutations affecting signaling through the NFkB pathway such as the alymphoplasia ( aly/aly ) mice develop chronic autoimmunity resembling Sjorgren’s syndrome despite impaired mTEC development and reduced numbers of tDC subsets [30, 31], again suggesting that severe disruptions of more than one subsets of thymic APCs are required for development of autoimmunty. Consistent with this, it was shown that depletion of DCs down to 5% of physiologic levels can still efficiently induce tolerance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR for quantification of salivary protein 1, C-reactive protein, and Hprt was performed as described previously (14).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Both cell types are functionally and phenotypically different. The mTEC together with DC have a special roll in eliminating auto-reactive T-cell clones through negative selection, as well as helping to regulate the production of regulatory T (T reg ) cells involved in prevention of autoimmune responses (Osada et al 2006;Mouri et al 2014;Ucar & Rattay 2015).…”
Section: Introductionmentioning
confidence: 99%